Effect of Ultrasonic Flexural Vibration on Solidification Structure and Mechanical Properties of Large-Size 35CrMoV Cast Ingot. (26th June 2019) - Shi, Chen; Li, Fan; Wu, Yongjun; Mao, Daheng
Abstract : In order to improve the performances of large-size 35CrMoV cast ingot, ultrasonic flexural vibration was guided into 35CrMoV steel melt through L-shaped ultrasonic waveguide rod during the solidification, and the effects of ultrasonic flexural vibration on macrostructure, microstructure, and mechanical properties of large-size 35CrMoV cast ingot were investigated. It is found that the columnar crystal zone has disappeared and the ingot is composed of the equiaxed crystals present in the ultrasonic ingot. The size of grains treated by ultrasonic are significantly smaller than conventional ingot. The distribution of ferrite in matrix structure is also more uniform than conventional ingot. The tensile strength is increased by 3.14%∼17.12%, and the elongation is increased by 39.13%∼287.50% compared with the conventional ingot at different positions.